PENGEMBANGAN PERANGKAT PEMBELAJARAN MANDIRI BERBASIS SOAL TERBUKA DALAM PEMBELAJARAN KALKULUS PRODI PENDIDIKAN MATEMATIKA - Hardiyanto Hardiyanto (Journal of Educational Science and Technology (EST), 2016)
The research aims was conducted to develop independent learning devices with open-questfon basis in fomrs of Satuan Acara Perkuliahan (SAP) or Course Unit and Module. The development process of independent learning devices with open-questions basis refered to Plomp's development model, namely: (1) Preliminary Investigation Phase, consisted of theoretical literature study, learning problem analysis, curriculum analysis, students’ characteristics analysis, and conceptual analysis; (2) Design phase, where the researcher designed the necessary learning devices and research instruments; (3) Realization/ Construction phase, where the researcher produced the learning devices amd research instruments based on the design form of the design phase; (4) Test, evaluation and revision phase, conducted in two main activities: (a) Learning devices validation, and (b) Trial process. The results of development of learning devices reveal that: (1) the learning devices have met validation criteria (valid: 2.5 ≤ M ≤ 3.5) based on validation average score of two assessors on SAP is 3.48, and the module is 3.42, (2) the development of learning devices have met the practical criteria (implemented entirely: 1.5 ≤ M ≤ 2.0) based on the average score of learning implementation aspect from two observer, 1.54; (3) the development of leaming devices is stated as effective because the students' classical learning completeness is 87% which have met the completeness criteria, where minimal 85% of the sfudents, 24 students or 61% of them obtain creative score above minimal standard of 65, students' activity can be stated as ideal because each activity is in the tolerant given time, and 75% of the students give positive response to learning instruments and learning process.